Training in the management of the acutely ill medical patient - McAuley, Danny (Clin Med (Lond), 2002)
The care of acutely ill patients constitutes an important and increasing part of hospital practice. However, the care of the acutely ill by general physicians without adequate training in intensive care medicine is cause for concern. This article identifies ways in which the recognised deficiencies in the care of the acutely ill medical patient can be improved.